2009
DOI: 10.1029/2009gb003472
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic production of nitrous oxide in the context of changing atmospheric levels

Abstract: [1] We use transit time distributions calculated from tracer data together with in situ measurements of N 2 O to estimate the concentration of biologically produced N 2 O ([N 2 O] xs ) and N 2 O production rates in the central North Atlantic Ocean. Our approach to estimation of N 2 O production rates integrates the effects of potentially varying production and decomposition mechanisms along the transport path of a water mass. We find that previously used approaches overestimate the oceanic equilibrium N 2 O co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 33 publications
(61 reference statements)
4
54
0
Order By: Relevance
“…This approach is highly suitable for calculating ΔN 2 O in waters in surface layers, but neglects the effect of the age of the water mass and, therefore, the variable atmospheric mole fraction that is involved in establishing an initial "equilibrium" (Walter et al, 2006;Freing et al, 2009). Nevison et al (2003) asserted that the use of only the contemporary atmospheric mole fraction introduces an uncertainty of 10-15% in the estimate of ΔN 2 O.…”
Section: In Situ Biological Productionmentioning
confidence: 99%
“…This approach is highly suitable for calculating ΔN 2 O in waters in surface layers, but neglects the effect of the age of the water mass and, therefore, the variable atmospheric mole fraction that is involved in establishing an initial "equilibrium" (Walter et al, 2006;Freing et al, 2009). Nevison et al (2003) asserted that the use of only the contemporary atmospheric mole fraction introduces an uncertainty of 10-15% in the estimate of ΔN 2 O.…”
Section: In Situ Biological Productionmentioning
confidence: 99%
“…The correlation between AOU and NO − 3 suggested that nitrification is the main process producing N 2 O (Elkins et al, 1978), given the ubiquitous presence of O 2 in the ocean (Yoshinari, 1976). Recently, a depth relationship and experimental results have been incorporated to improve models so that they reliably predict N 2 O concentrations and atmospheric exchange (Butler et al, 1989;Suntharalingam et al, 2000;Nevison et al, 2003;Freing et al, 2009). However, N 2 O consumption by denitrification in the OMZ has not been included in these models, leaving part of the N 2 O cycle unresolved (Nevison et al, 2003).…”
Section: Existing N 2 O Models For the Omzmentioning
confidence: 99%
“…Models of N 2 O in the OMZ are based on the premise that N 2 O is produced by nitrification and denitrification according to O 2 concentrations observed in the ocean (Nevison et al, 1995;Suntharalingam et al, 2000;Freing et al, 2009). These models are supported by both experiments of N 2 O production by nitrification (Goreau et al, 1980) and estimations of in-situ N 2 O production by denitrification resulting in increasing N 2 O production as O 2 decreases (Kester et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As in Freing et al (2009), we estimate N 2 O eq (the N 2 O concentration derived from equilibrium with atmospheric N 2 O when the water was last in contact with the atmosphere) as follows:…”
Section: Calculating N 2 O Production Ratesmentioning
confidence: 99%
“…Here, we account for historic increases in atmospheric N 2 O using the transit time distribution (TTD) method described in Freing et al (2009) and Waugh et al (2003) (see the Appendix for a more detailed description of the TTD method as applied here). Similarly to Waugh et al (2003), we assume that a water parcel is a mixture of water with various ages, and that the density distribution of these ages can be described using an Inverse Gaussian distribution of the form:…”
Section: Calculating N 2 O Production Ratesmentioning
confidence: 99%